Occupational Safety and Health Management System (OSHMS) in Health Care Facilities of Sekadau Health Center, Sekadau Hilir Subdistrict: Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di Fasilitas Pelayanan Kesehatan Puskesmas Sekadau Kecamatan Sekadau Hilir - Jumiati Safitri; Selviana; Elly Trisnawati; Ayu Rizky (Muhammadiyah Institute of Technology and Health, West Kalimantan (ITEKES Muhammadiyah Kalimantan Barat), 2024)
Background: Health services in Health Care Facilities (Fasyankes) have high risks related to the safety of patients and health workers, which can trigger occupational accidents. Risk control through the implementation of the Occupational Safety and Health Management System (OSHMS) is needed to create a safe and healthy work environment. Objective: This study aims to identify and evaluate the implementation of occupational health and safety management systems in health care facilities, especially in Sekadau Health Center. Methods: This research is a descriptive study with a crosssectional design. Data were collected through observation and validated based on interviews with occupational health program holders, health and safety programs, and doctors. Results: This study shows that the implementation of the Occupational Safety and Health Management System (OHSMS) at the Sekadau Health Center mostly runs quite well, especially in policy setting, planning, and reviewing and improving OHS performance. The implementation of the OHS Plan has gone very well. However, weaknesses were found in monitoring and evaluating OHS performance. Conclusion: It is recommended that the Sekadau Health Center strengthen monitoring and evaluation of OHS performance by adding resources and experts in the field of occupational safety and health, to ensure a more thorough and sustainable implementation.